An optimization method applied to active solar energy systems for buildings in cold plateau areas – The case of Lhasa. (15th May 2017) - Si, Pengfei; Feng, Ya; Lv, Yuexia; Rong, Xiangyang; Pan, Yungang; Liu, Xichen; Yan, Jinyue
Highlights: Develop an optimization model for integrated solar energy systems. Apply the model to a typical office building located in Lhasa. PV systems are superior to solar thermal systems in cold plateau areas. Financial subsidies influence the system more than commercial electricity prices. Conduct LCA to compare performances of an optimal system and a conventional one. Abstract: Solar energy for building applications may significantly reduce the conventional energy consumption and the related carbon dioxide emissions. The comprehensive utilization of integrated solar thermal and photovoltaic systems is undoubtedly a subject of interest. In the present paper, an optimization model was proposed for integrated solar energy systems, aiming to figure out the optimal utilization and economical efficiency of solar energy resources for buildings in cold plateau areas. A case study in Lhasa city was further carried out in order to evaluate the energy and economic performance of the developed model. The results indicated that solar photovoltaic systems are preferred than solar thermal systems for typical office buildings in cold plateau areas with rich solar energy resources. In addition, a sensitivity analysis was performed to investigate the influences of financial subsidies and commercial electricity prices on the system economical performance. Furthermore, life cycle assessment was conducted to compare and analyze the performances of an optimization system and a conventional system.